Nutritional Status and Health among Elderly People in Chandragiri Municipality - Keshab Parajuli (Journal of Population and Development, 2026)
This paper based on nutrition status and health among elderly people of Nepal. the ageing is associated with a variety of physiological and metabolic alterations that increase the risk of chronic diseases, presenting hypertension as an important public health problem in the elderly population. Th aimed of the study is to find out nutritional status and health among elderly people. The community-based analytical cross-sectional study was conducted among 418 participants aged 60 years and older was randomly selected through a multistage random sampling process. The data were collected through un-interfered face to face interview using pretested semi-structured questioners, and the collection of anthropometric and blood pressure measurements by following standard protocol There was significant gender variation across age groups, in which males were predominant in most ages, especially in the population of over 75 years. The suboptimal fruit intake was reported by over half the sample based on dietary assessment, although vegetables were consumed regularly. Majority of the respondents took meals at home, had not added more salt and predominantly used sunflower oil for cooking which showed a lack of dietary variety. The high prevalence of co-morbidities was noted, but except for arthritis, asthma, depression and stroke, none of the co-morbidities had a significant association with hypertension. The notable result was the strong relationship of hypertension and parental history of hypertension. The prevalence of hypertension in the elders with hypertensive parents was markedly higher than that without hypertensive parents, which further indicated a genetic predisposition and shared lifestyles.